Magneto, Spectral and Thermal Studies on Co2+, Ni2+, Cu2+, Zn2+, Cd2+, UO22+ and VO2+ chelates of o-[N-α-pyridimino) phenol and o-(N-α-pyrrolidimino) phenol. - Sharma, Anju; Choudhary, Vimla; Sharma, Shobha (Asian Journal of Chemistry, 2010)
Solid chelates of Co2+, Ni2+, Cu2+, Zn2+, Cd2+, UO2+2 and VO2+ with o-(N-α-pyridimino) phenol (H2PP) and o-(N-α-pyrrolidimino) phenol (H2PP´)have been synthesised and characterised by different physico-chemical techniques. Elemental analysis, magnetic, conductance, spectroscopic (electronic, IR and 1H MNR) and thermal studies conducted on solid chelates suggest an octahedral stereochemistry for Co2+, Ni2+, UO2+2 and VO2+ chelates. Various bonding parameters were also evaluated.